The Syrian refugee crisis in Jordan: a cross sectional pharmacist-led study assessing post-traumatic stress disorder - Basheti IA; Ayasrah SM; Basheti MM; Mahfuz J; Chaar B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: The United Nations has declared the Syrian crisis as the worst humanitarian crisis of the twenty-first century. Pharmacists play a vital role in humanitarian aid and in delivering health advices for refugees. Many Syrian refugees are in need of psychosocial assessments. Objective: Objective of this study was to investigate the prevalence of post-traumatic stress disorder (PTSD), assessed by pharmacists among Syrian civilian refugees residing in Amman, Jordan. Methods: A cross-sectional study involving Syrian civilian refugees living in Amman, Jordan, was conducted using the published and validated Arabic version of the Harvard Trauma Questionnaire (HTQ). Pharmacists recruited civilian Syrian refugees and completed the HTQ. The questionnaire included 45 questions, with the first 16 questions (HTQ-16) intended to assess the trauma symptoms felt by refugees. Assessments were done by the pharmacists and refugees were categorized to suffer PTSD if their mean item score for the HTQ-16 scale was > 2.5. Results: Study participants (n=186; mean age 31.5 years; 51.3% males) had a HTQ-16 mean score of 2.35 (SD=0.53), with a range of 1.19 - 3.63. Over a third of participants (38.7%) were categorized as having PTSD. Males reported significantly worse PTSD symptoms (mean=2.42, SD=0.50) compared to females (mean=2.26, SD=0.57). Correlation between the mean item score for the HTQ-16 and characteristics of the study participants showed higher mean item score correlated with being a male, older in age, a smoker, and if trauma was experienced. Conclusions: Many Syrian civilian refugees living in Jordan suffer from PTSD. Male participants were found to be more affected by the severity of the disorder. Pharmacists are suitably situated to identify civilian Syrian refugees suffering from PTSD in dire need of help, paving the way for much needed healthcare resources to be delivered to this particular group of refugees.